A COMPARATIVE ANALYSIS OF LANGUAGE FEATURES ACROSS COMMUNICATIVE ENGLISH SKILLS AND GARMENT VOCATIONAL TEXTS - Shewangizaw, Gashaw; Hailu, Alemu; Haile, Wondu (Celtic : A Journal of Culture, English Language Teaching, Literature and Linguistics, 2024)
Linguistic variations across academic and professional domains highlight the need for English for Specific Purposes (ESP) curricula tailored to technical communication demands. This study aims to analyze discourse characteristics in Communicative English Language Skills texts and Garment and Apparel Fashion materials to identify genre-based distinctions. Purposive sampling was used to select relevant courses, and quantitative register analysis was conducted using adapted multidimensional frameworks to identify patterns in vocabulary, grammar, and discourse types. The findings revealed that Garment and Apparel Fashion texts emphasized descriptive, instructional, and analytical functions essential for skill development, while Communicative English Language Skills texts incorporated a broader range of genres to foster versatility. These variations in discourse features were contextually driven and informed the need for curriculum refinement. The study emphasizes the importance of evidence-based, context-sensitive English instruction to address disciplinary discourse differences.